Contamination of Ocean as a Result of Ground Sources (International Journal of Innovative Research in Computer Science & Technology, 2022)
- Anthropogenic and population increase in  the River In china river basin and coastal regions have  placed great pressure upon that East China Sea (ECS)  ecology. Poor resource stewardship and short-term  economic goals have resulted in significant environmental  degradation, presenting a danger to coastal communities'  health and well-being. Nitrogen, salt, tar hydrocarbons,  organic detritus, and heavy metals are the primary  contaminants. Nutrients cause eutrophication in marine  and estuarine habitats, resulting in red tides. The decline of  the River Basin does have a direct influence on the ECS's  aquatic environment. Stable current from the canal, along  with tidal salty water in the estuary and sediment burdens  from the river, prevents ocean degradation in the floodplain  and its surrounding coastal region. This base would be  altered by large-scale water transfer and dam development  in the Yangtze River. The ECS must protect the  environment by counteracting harmful processes.  Integrating human and ecological decision-making is the  most challenging problem. To address these challenges, a  deeper knowledge of the social factors that generate  environmental stresses is required. International  cooperation will significantly aid development, especially  in terms of financial, technological, scientific, and people  resources.
Keywords: Acidification; Chemicals; East China Sea; Eutrophication; Ocean Pollution